BERANGKAT DARI MASA KANAK-KANAK - Mazianaomi, Yolanda; Sanjaya, Tisna (Visual Art, 2012)
Abstrak Masa kanak-kanak adalah masa-masa yang indah dan penuh warna namun merupakan masa yang paling rentan juga dalam kehidupan manusia sebagai titik awal pemberangkatan manusia menuju sebuah pribadi yang utuh. Dalam pengerjaan Tugas Akhir ini, penulis mencoba menggambarkan masa kecil sebagai fase penting dalam kehidupan manusia dalam membentuk sebuah kepribadian dalam diri individu. Hasil pengerjaan karya adalah drawing di atas kain dengan medium berbasis air yang dipadukan dengan benang sebagai tujuan menyajikan masa kecil yang ironis tersebut menurut pandangan pribadi penulis. Kata Kunci :childhood, drawing, kepribadian, organis, perkembangan, stitching Â  Abstract Childhood are the beautiful and colourful moments but it is also the most vulnerable time in human life, where it was our starting point as a person, a growing up phase where a person becomes a full individual. In this final assignment, the author try to portray childhood as an important phase in humanâs life in shaping the personality of an individual. The result is a drawing on fabric with water-based medium combined with stitching technique using threads as the purpose of serving the ironism of childhood accordance to authorâs opinion.